Jawabanmu

2014-03-28T21:55:17+07:00
h(x)=ax + 3
h(1)=ax + 3 = 2
      = a(1) = 2 - 3
         a = -1

h(x)= -1 (5) + 3
     = -2
h(x) = ax+b
h(x) = ax + b
h(3) = 3a + b = 13
h(-1) = -a +b = 1 dieliminasi
4a = 12
Jadi a=3 maka b=4
h(5) = 5a + b
= 5(3) + 4
= 19
Jawaban paling cerdas!
2014-03-28T22:03:23+07:00
H(3) = a.3 + b =13          h(3) = 3.3 + b = 13
h(-1)= a.-1 + b = 1                = 9    + b = 13
      = (3a-(-1a)) =12              = b          = 13-9
      = 4a          = 12             = b           = 4
       = a          = 3

h(5) = 5.a + b = 5.3 + 4 = 15 + 4 = 19

diperiksa lagi kalau ada kesalahan :) senang bisa membantu
2 5 2